PENGARUH FORMULASI CARBOXYMETHYL CELLULOSE DAN ASAM STEARAT TERHADAP KARAKTERISTIK GEL BIOETANOL - Martaningsih Sutarsa, Ni Wayan Nadia; Admadi Harsojuwono, Bambang; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
Bioethanol gel is a mixture of bioethanol and gel, so this product is one of the bioenergy products being developed today. This study was conducted to determine the effect of the formulations of carboxymethyl cellulose (CMC) and stearic acid to the characteristics of bioethanol gel. To achieve the objective of this study, the experiment that was designed using a randomized complete design was done on a laboratory scale by the treatments of the proportion of CMC and stearic acid in the formulation. The data obtained were analyzed by analysis of variance and if the treatment affected on the observed variables then continued with Duncan test. Effectivity test of the observed variables was used to obtain the best characteristics of bioethanol product. The test result showed that 1 g of CMC and 2 g of stearic acid produced the best characteristics of bioethanol gel with viscosity of 10 cp, combustion residues of 0.412%, 0.040% ash content, and duration of flaming was 150.5 seconds per 5 g sample. The bioethanol gel had a thermal efficiency value of 59.64% and a calorific value expressed in higher heating value and lower heating value was 3,163.283 cal/g and 2,562.697 cal/g, respectively. Key words: carboxymethyl cellulose , stearic acid, bioethanol gel, bioenergy
Keywords: 138